Modelling annual scintillation arc variations in PSR J1643−1224 using the Large European Array for Pulsars. Issue 1 (18th January 2022) - Mall, G; Main, R A; Antoniadis, J; Bassa, C G; Burgay, M; Chen, S; Cognard, I; Concu, R; Corongiu, A; Gaikwad, M; Hu, H; Janssen, G H; et al.
ABSTRACT: In this work, we study variations in the parabolic scintillation arcs of the binary millisecond pulsar PSR J1643−1224 over five years using the Large European Array for Pulsars (LEAP). The two-dimensional (2D) power spectrum of scintillation, called the secondary spectrum, often shows a parabolic distribution of power, where the arc curvature encodes the relative velocities and distances of the pulsar, ionized interstellar medium, and Earth. We observe a clear parabolic scintillation arc, which varies in curvature throughout the year. The distribution of power in the secondary spectra is inconsistent with a single scattering screen, which is fully 1D or entirely isotropic. We fit the observed arc curvature variations with two models: an isotropic scattering screen and a model with two independent 1D screens. We measure the distance to the scattering screen to be in the range 114–223 pc, depending on the model, consistent with the known distance of the foreground large-diameter H ii region Sh 2-27 (112 ± 17 pc), suggesting that it is the dominant source of scattering. We obtain only weak constraints on the pulsar's orbital inclination and longitude of ascending node, since the scintillation pattern is not very sensitive to the pulsar's motion and the screen is much closer to the Earth than the pulsar. More measurements of this kind – where scattering screens can be associated with foreground objects – will help to inform the origins and distribution of scattering screens within our galaxy.